Makna Sinkronik-Diakronik Kata ‘Usr dan Yusr dalam Surat Al-Insyirāh - Mujahid, Ahmad (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2019)
This paper discusses the meaning of ‘Usr and Yusr on QS. Al-Insyirah: 5-6. To understand the meaning of a word or structure of Quranic verses is highly complex. Thus, understanding semantically becomes an alternative, that is to reveal the synchronous and diachronic meanings. This study explains two conclusions. Firstly, the basic meaning is a meaning that is absolutely attached to the intended word, without being able to be changed by anyone as long as there is an agreement between the speakers. In obtaining the basic meaning of the word 'usr there are several meanings, among others: oppression, distress, being poor and so on. While the word yusr has the meaning das` ar as follows: easy, gentle, and so on. While the relational meaning is the meaning will change according to the elements that accompany it. The word 'usr there is a new meaning of meaning when juxtaposed with other words, as follows: oppressive, blackmail, precarious, and so on. While the relational meaning of the word yusr has several meanings: left wing troops, available, giving birth easily. Second, synchronicity is research by focusing on one particular period, whereas diachronic is research by considering the development of language from one time to another, both before and after. Then in the meaning of the Qur'an simplified into three parts: Pre-Qur'anic, Qur'anic and third post-Qur'anic.